2013
DOI: 10.1007/s00394-013-0643-2
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of obesity and overweight and associated nutritional factors in a population-based Swiss sample: an opportunity to analyze the impact of three different European cultural roots

Abstract: Obesity and overweight affect almost half of the Swiss adolescents and adults, and the prevalence appears to increase. Using BMI and WC to define obesity led to different prevalences. Differences were furthermore observed across Swiss linguistic-cultural regions, despite a common socio-economic and governmental framework. We found a positive association between obesity and salt intake, with a potential deleterious synergistic effect on cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 37 publications
3
16
1
Order By: Relevance
“…[24][25][26] Also, a Swiss study found a positive association between obesity and salt intake. 27 This was also consistent with the policy and action on nutrition and health promotion in many countries. In the UK, a wide range of policies are in place, including support for breastfeeding and healthy weaning practices, nutritional standards in schools, restrictions on marketing foods high in fat, sugar and salt to children, schemes to boost participation in sport, active travel plans, and weight management services.…”
Section: Discussionsupporting
confidence: 77%
“…[24][25][26] Also, a Swiss study found a positive association between obesity and salt intake. 27 This was also consistent with the policy and action on nutrition and health promotion in many countries. In the UK, a wide range of policies are in place, including support for breastfeeding and healthy weaning practices, nutritional standards in schools, restrictions on marketing foods high in fat, sugar and salt to children, schemes to boost participation in sport, active travel plans, and weight management services.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, the current study observed that participants with obesity had higher Na excretion than those without. This finding is in line with previous studies (8) , but inconsistent with the finding of a cross-sectional study of 1008 students in grade 7 in Canada (11) . The inconsistency could be in part due to Na intake estimated by 24 h diet recall.…”
Section: Discussioncontrasting
confidence: 54%
“…Previous studies have identified that high Na intake is a risk factor for CVD incidence and mortality (6,7) . Although several studies, attempting to examine the relationship between high Na intake and risk of obesity, have been conducted globally (8)(9)(10)(11)(12) , detailed analyses evaluating the risk of high Na intake estimated by 24 h urinary Na excretion on obesity have been limited (8,12) . Additionally, only one previous study explored the association between Na:K estimated by earlymorning first-void urine samples and total-body percentage fat measured by dual-energy X-ray absorptiometry (13) .…”
mentioning
confidence: 99%
“…In the population-based Swiss Salt Study (2010-2011), which also relied on measured anthropometric data and included 1505 participants aged 15 years and over, average BMI was 25.2 kg/m 2 (39). In the population-based CoLaus study, including more than 6100 adults residing in the city of Lausanne and aged 35 to 75 years, average BMI at baseline (2003-2006) was 25.8 kg/m 2 (14).…”
Section: Discussionmentioning
confidence: 99%